Is the LOD cloud at risk of becoming a museum for datasets? Looking ahead towards a fully collaborative and sustainable LOD cloud. - Debattista, Jeremy; Attard, Judie; Brennan, Rob; O'Sullivan, Declan (My University, 2019)
The Linked Open Data (LOD) cloud has been around since 2007. Throughout the years, this prominent depiction served as the epitome for Linked Data and acted as a starting point for many. In this article we perform a number of experiments on the dataset metadata provided by the LOD cloud, in order to understand better whether the current visualised datasets are accessible and with an open license. Furthermore, we perform quality assessment of 17 metrics over accessible datasets that are part of the LOD cloud. These experiments were compared with previous experiments performed on older versions of the LOD cloud. The results showed that there was no improvement on previously identified problems. Based on our findings, we therefore propose a strategy and architecture for a potential collaborative and sustainable LOD cloud.
PUBLISHED
Keywords: Linked Data; metadata quality; data quality; sustainable services